Ammonia-Assimilating Bacteria Promote Wheat (Triticum aestivum) Growth and Nitrogen Utilization - Yuqian Gao; Qi Zhang; Yuannan Chen; Yanqing Yang; Chenxiao Zhou; Jiayang Yu; Yanan Li; Liyou Qiu (Microorganisms)
Nitrogen fertilizers in agriculture often suffer losses. Ammonia-assimilating bacteria can immobilize ammonia and reduce these losses, but they have not been used in agriculture. This study identified an ammonia-assimilating strain, Enterobacter sp. B12, which assimilated ammonia via the glutamate dehydrogenase (GDH) pathway at low levels (5 mM) and the glutamine synthetase (GS)-glutamine-2-oxoglutarate aminotransferase (GOGAT) pathway at high levels (10 mM). Inoculating wheat with B12 increased seedling dry weight, nitrogen accumulation, rhizosphere soil nitrogen content, and root enzyme activities, including GDH, superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD), under both conditions. However, root GS, GOGAT enzyme activities, and ammonia assimilation-related gene expressions were lower than the controls. The results suggest that the ammonia-assimilating bacterium promotes wheat growth, nitrogen accumulation, and soil nitrogen immobilization by establishing an ammonia and amino acid exchange with roots and enhancing root antioxidant capacity, making it a potential plant growth-promoting rhizobacteria (PGPR).